Mitigating Supply Chain Risks in The Traditional Beverage Industry with The House of Risk (HOR) Method - Alam, Sairul; Putri, Riri Ramadhani; Hartini, Sri (Jurnal Ilmiah Teknik Industri, 2025)
The production process of wedang uwuh at MSMEs XYZ frequently encounters interruptions caused by a scarcity of raw materials from a limited supplier base. This research employs the House of Risk (HOR) method to identify risks, prioritize risk agents, and formulate mitigation solutions. During the initial phase of HOR, 27 risk events and 30 risk agents were found, with 15 priority risk agents determined by a cumulative Aggregate Risk Potential (ARP) value of 81%. During the second phase of HOR, 24 mitigation strategies were developed, with the foremost five being: (PA14) routine equipment inspection and maintenance; (PA1) systematic sales documentation; (PA4) partnership with large farmers/suppliers; (PA11) standard operating procedures in the mixing process; and (PA13) formulation of adaptable contracts with suppliers concerning volume and delivery timelines. The execution of these mitigation techniques is anticipated to improve operational efficiency and supply chain resilience at XYZ MSMEs in addressing current concerns.